NMR-based metabolomics for elucidating the bioactive compounds from Mangifera caesia Jack and Ficus auriculata lour - Mohamed Yunus, Siti Norhamimah; Abdul Hamid, Nur Ashikin; Jaafar, Ahmad Haniff; Lawal, Umar; Abas, Faridah (Wiley-Blackwell Publishing, 2021)
Mangifera caesia and Ficus auriculata are neglected fruits found in Malaysia and are locally known as “buah binjai” and “buah ara”, respectively. To profile the metabolites for both fruits, we conducted a robust 1H-nuclear magnetic resonance (NMR)-based metabolomics approach. Principal component analysis (PCA) and partial least square (PLS) analyses were applied to distinguish the metabolites variations of M. caesia and F. auriculata fruits extracted with different ethanol ratios (0, 70, and 100%). In total, 34 metabolites were identified in M. caesia and F. auriculata fruits. The 70% ethanol extracts of both fruits displayed the highest antioxidant and α-glucosidase inhibitory activities, as well as notable with the highest phenolic content, compared with the other samples. The present metabolomics study shows that the polarities of solvent extractions play a crucial role in the assessment and recovery of the metabolites for the high value of natural antioxidants and α-glucosidase inhibitors in M. caesia and F. auriculata fruits.